Control of suddenly expanded flows from correctly expanded and under expanded nozzles at supersonic mach number for area ratio 2.56 - Bashir, Musavir; Baig, Maughal Ahmed Al; Ismail, Ahmad Faris; Khan, Sher Afghan (IOSR journals, 2016)
Airflow from convergent-divergent axisymmetric nozzles expanded into circular duct of higher area were studied experimentally, with the main focus on the flow development in the duct. The flow parameters considered in this investigation are the Mach number at the nozzle exit and the level of expansion. The geometrical parameters considered are the area ratio and the L/D ratio of the duct. To control on the flow field developed in the duct, four tiny jets of 0.5 mm radius located at 90 degrees intervals at 6.5 mm radius from the centre of the nozzle exit were employed as the flow regulators. The Mach number in this case was 1.48. The area ratio of the study was 2.56. The nozzle pressure ratio (NPR) used was from 3.27 and 5.35 respectively which corresponds to ideally expanded and under expanded cases. The L/D ratio of the enlarged duct was varied from 10 to 1. From the results it is found that there is a jump in the wall pressure when flow passes through first oblique shock and this trend is repeated for all the cases.From the results it is found that the entire flow field is full of waves and flow remains identical with and without control when the jets were operated under favourable and adverse pressure gradient, it is also observed that when flow regulators in the form of tiny jets are employed they do not disturb the flow of duct.